INFLUENCE OF INTERNET GAMES ON YOUNG PEOPLE'S MIND AND ITS NEGATIVE ASPECTS ("Conference on Universal Science Research 2023", 2023)
This article talks about the impact and negative aspects of internet games that have entered our lives and society on the minds of young people.